Short-Term Health Effects Of Copper, Lead And fire Smoke On Sprague-Dawley Rats - Navappan, Mageshwary (2006)
The toxicological effects of copper, Cu, lead, Pb, and fire smoke were determined comparatively in this study. Cu and Pb were selected due to their abundance in ambient air bound to conjugates of PMlO (US EPA, 1986). Cu is released to the atmosphere in association with particulate matter (Dameron and Howe, 1998; ATSDR, 2004). The level of Pb in the air is considerably high in the urban region especially due to automobile emission and industrial wastes. Smoke from open burning contains particulate matters that conjugate with Pb emitted from the automobile fires. contamination by Pb and Cu, besides a few other metals, appears to be significant in water runoff from these types of fires (Lonnermark and Blomquist, 2005). Attempts were made at determining the effects of these three types of environmental pollutants, namely, copper, lead and fire smoke on three independent groups of Sprague-Dawley rats. Thirty-two 11-week-old rats (16 male and 16 female) were allocated each for copper and lead treatment groups. Fifty rats (25 male and 25 female) were allocated for the fire smoke exposed group. The copper and lead administered groups were subdivided into 4 different concentrations, being 0 parts per million (ppm), 200 ppm, 350 ppm and 500 ppm respectively. Copper was administered in the form of copper(I1) sulphate solution while lead in the form of lead acetate solution, both orally in fixed volumes of 250 mL and ad libitum for 4 consecutive days during which all rats were closely monitored for macroscopic lesions and behavioural abnormalities. The rats were anaesthetised for cardiac puncture via which adequate volume of blood was collected for serum chemistry to determine levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), cholesterol, albumin, triglyceride, high density lipoprotein (HDL), low density lipoprotein (LDL), blood urea nitrogen (BUN) and total protein and to prepare thin blood smears for differential white blood cell (WBC) counts. The liver and kidney specimens were subjected to macrosopic and microscopic examinations. The modes of exposure for the fire smoke treated rats was via inhalation and ingestion of the particulate matters found in the smoke that sediments into the drinking water or feed of the rats. Smoke was induced in a microenvironment (with a volume of 2.16 m3) in which the rats were exposed for 4 consecutive days. These rats and their relevant specimens were also subjected to similar macroscopic and microscopic examinations. Basically, the concentrations of the selected serum parameters in all control rats were not observed to be within the reference range. In the treated groups (all three categories), a common dose-response relationship could not be generated from the readings obtained. No significant difference was observed statistically (based on ANOVA) among the readings of serum parameters in rats given 200 ppm, 350 ppm and 500 ppm of copper@) -- -- .- - - - -- sulphate to that of the control rats except the mean of ALP concentration. It was significantly different from the control group at p< 0.05. The lead acet-a-te - - - - treated rats showed significant differences among the groups given 200 ppm, 350 pprn and 500 ppm in their levels of ALT, AST, ALP, cholesterol and HDL with p-values of 0.013, 0.009, 0.034, 0.002 and 0.003 respectively (The mean difference is significant at ~ ~ 0 . 0 5T.h)e re was not any detectable amount of copper and lead in the samples of fire smoke including water samples that were directly exposed to the smoke. The fire smoke exposed rats showed significant differences in AST, ALP, albumin and triglyceride HDL with pvalues of 0.003, 0.006, 0.006 and 0.000 respectively (the mean difference is - significant at p<0.05). None of the rats from the treated or exposed groups showed abnormal WBC count when compared to the reference range. There was no statistical significance either when compared to the control group of rats at p<0.05. No marked macroscopic or microscopic lesion was observed in almost 96% of the rats experimented with their liver and kidney specimens. The cholesterol level was significantly increased in all rats including that of the control rats. Conclusions are made that a short-term exposure of 4 days did not induce any significant toxicokinetics that could affect the health of the treated rats. An association between the toxicity of copper, lead and fire smoke cannot be made either because there was no detectable amount of copper or lead in the fire smoke.